PENGARUH MODEL PEMBELAJARAN GAMIFIKASI TERHADAP STUDENT ENGAGEMENT DAN WAKTU AKTIF BELAJAR PADA PEMBELAJARAN BOLA VOLI - Hendra Jaya; Ahmad Rizal; Muhammad Ali Ode (STKIP Melawi, 2026)
Abstract: This research examines gamification's impact on student involvement and active learning duration in volleyball instruction. A quasi-experimental pretest-posttest control group design involved 60 Grade X participants divided into treatment and comparison groups. The treatment group received intervention integrating point systems, achievement badges, ranking boards, and progression mechanisms via Classcraft platform, while the comparison group followed conventional approaches. Measurements employed the Physical Education Classroom Instrument for assessing student involvement and System for Observing Fitness Instruction Time for observing active learning duration. Findings revealed the treatment group experienced 24.04% increased student involvement and 43.85% elevated active learning duration, contrasting minimal improvements in the comparison group. Independent sample t-test analysis confirmed significant disparities between groups (p < 0.001, Cohen's d > 2.8). Conclusively, gamification effectively enhances behavioral, emotional, cognitive involvement while optimizing instructional time allocation in physical education, particularly for volleyball skill acquisition. Keywords: gamification, student engagement, active learning time, volleyball learning, physical education Abstrak: Riset ini bertujuan menganalisis dampak implementasi gamifikasi terhadap keterlibatan siswa dan durasi pembelajaran aktif dalam mata pelajaran bola voli. Metode kuasi-eksperimental dengan desain pretest-posttest control group melibatkan 60 peserta didik kelas X yang terbagi dalam kelompok perlakuan dan pembanding. Kelompok perlakuan memperoleh intervensi pembelajaran mengintegrasikan komponen poin, lencana prestasi, papan peringkat, dan sistem penjenjangan melalui platform Classcraft, sedangkan kelompok pembanding mengikuti pendekatan konvensional. Pengukuran menggunakan Physical Education Classroom Instrument untuk menilai keterlibatan siswa dan System for Observing Fitness Instruction Time untuk mengobservasi durasi pembelajaran aktif. Temuan menunjukkan kelompok perlakuan mengalami kenaikan keterlibatan siswa 24,04% dan durasi pembelajaran aktif 43,85%, kontras dengan peningkatan minimal kelompok pembanding. Analisis independent sample t-test mengonfirmasi disparitas signifikan antarkelompok (p < 0,001, Cohen's d > 2,8). Kesimpulannya, gamifikasi terbukti efektif meningkatkan keterlibatan behavioral, emosional, kognitif serta mengoptimalkan alokasi waktu instruksional dalam pendidikan jasmani khususnya penguasaan keterampilan bola voli. Kata Kunci: gamifikasi, student engagement, waktu aktif belajar, pembelajaran bola voli, pendidikan jasmani